Management issues in planning, design and construction of sewerage treatment plants - 273718 Yap, Jit Ming; Zainai Mohamed, supervisor; Fakulti Kejuruteraan Awam (2000)
Thesis (Sarjana Kejuruteraan (Pengurusan Kejuruteraan)) - Universiti Teknologi Malaysia, 2000